2019
DOI: 10.3329/jbau.v17i3.43225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage temperatures on the quality parameters of fish condiment prepared from Thai pangus (Pangasianodon hypophthalamus)

Abstract: Quality parameters of a fish/food product changes with the storage temperature. Therefore, the present study was carried out to evaluate the effect of different storage temperatures on the changes in chemical and microbiological parameters of fish condiment prepared from Thai pangus (Pangasianodon hypophthalmus). The study was conducted in the Department of Fisheries Technology Laboratory from October 2015 to September 2016.Standard methodologies for product preparation and other analyses (chemical and microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Dhar and Karthikeyan (2014) found the peroxide value increased with the storage period for pickle from small freshwater prawn (Macrobrachium dayanam), which was similar to the present study. Hossain et al (2019b) reported a similar increasing trend in peroxide value for pangas condiment at room temperature (28°C to 32°C) during 15 days of storage.…”
Section: Figmentioning
confidence: 52%
“…Dhar and Karthikeyan (2014) found the peroxide value increased with the storage period for pickle from small freshwater prawn (Macrobrachium dayanam), which was similar to the present study. Hossain et al (2019b) reported a similar increasing trend in peroxide value for pangas condiment at room temperature (28°C to 32°C) during 15 days of storage.…”
Section: Figmentioning
confidence: 52%
“…The impact of varying ranges of water temperature on growth efficiency was examined by Kausar and Salim (2006). The water temperatures in the ponds on the BAU campus in Mymensingh were measured by Hossain (2004) and ranged from 29.4 to 33.0 ºC and 26.0 to 32.8 ºC, respectively. According to measurements made by Alam (2009) and Hossain (2009), the temperature of the water in Agro 3 Farm's ponds in Trishal, Mymensingh, ranged from 26.9 to 32.5 ºC.…”
Section: Water Quality Parametermentioning
confidence: 99%